Isolation and characterisation of four novel bacteriophages infecting clinically relevant PCR ribotypes of Clostridium difficile - Whittle, Michaella (2018)
Clostridium difficile infection is the leading cause of antibiotic-associated diarrhoea in North America and Europe. The disease is most commonly treated with only a handful of antibiotics, amongst those vancomycin, a so-called last resort therapy. Growing concerns over antibiotic resistance have led to the desire for more targeted therapies. In this study, we report the isolation and characterisation of four novel bacteriophages, ΦCD08011, ΦCD2301, ΦCD418 and ΦCD1801, able to infect a range of clinically relevant C. difficile PCR ribotypes. The four phages belong to the Myoviridae family of tailed phages, established through the use of transmission electron microscopy and the identification of key genes within their genomes. Host range analysis of the four phages showed that phage ΦCD1801 had the broadest host range, able to infect and lyse all but one of the PCR ribotype 078 isolates tested. Further growth rate characterisation, rate of attachment and determination of burst size were also completed. Finally, SlpA, the main component of C. difficile’s S-layer, was confirmed as the bacterial receptor for this phage. The presence of slpA from the S-layer cassette of PCR ribotype 078 C. difficile strains conferred ΦCD1801 binding to an otherwise resistant strain. These findings will be instrumental in the ability to expand C. difficile phage host range to allow more targeted phages for the treatment of C. difficile infections.